Do government outlays crowd-out private consumption? Evidence from the European Union - Ömer Faruk Bölükbaşı; Olcay Çolak (PLoS ONE, 2026)
The relationship between private consumption expenditure and public expenditure represents a recurring theme in macroeconomics, with relevance to both empirical and theoretical discourse. However, there is a lack of consensus on its direction. Accordingly, this study aims to examine whether public expenditure rules out private consumption expenditure for European Union during the period of 1995–2022. The findings indicate that public expenditure has a positive effect on private consumption expenditure over the long term, thereby corroborating Keynesian theory. However, except the defense expenditure, the findings demonstrate the complementary effect of public expenditures on private consumption expenditures. Moreover, disposable income has a positive influence in all model specifications, which corroborates the Keynesian Absolute Income Hypothesis. Considering the findings, this study also suggests some policy recommendations for the future.